A study of the machining characteristics of AISI 1045 steel and Inconel 718 with a cylindrical shape in laser-assisted milling. (5th December 2015) - Woo, Wan-Sik; Lee, Choon-Man
Abstract: Laser-assisted machining (LAM) is an effective and economic technique for enhancing the machinability of materials which are difficult-to-cut, such as nickel alloys, titanium alloys and various ceramics. Recently, many researchers have studied the effectiveness of laser-assisted turning (LAT) by measuring its cutting force, tool wear, specific cutting energy and surface roughness. However, research on laser-assisted milling (LAMill) is still in progress because it is difficult to control the laser heating source and tool path to machine the varying shape of the workpiece using this method. Moreover, there have been no researches of workpieces with three-dimensional shapes. During the LAMill process, the material is softened and the mechanical strength of the material is reduced when a laser is used to irradiate the surface of the workpiece. As a result, the cutting force is reduced and the surface roughness is improved with LAMill. The purpose of this study was to develop three-dimensional LAMill and to verify the effectiveness of this approach by comparing it to the conventional machining (CM) method. A thermal analysis was also conducted in order to determine the effective depth of cut (DOC). Also, the cutting force and surface roughness of AISI 1045 steel and Inconel 718 with cylindrical shapes were measured. Measured results of machining characteristics were also analyzed according to the cutting method, i.e., up cut milling, down cut milling and milling style. Highlights: The materials with cylindrical shape is first applied to laser-assisted milling (LAMill). The method determining the depth of cut through thermal analysis is proposed. The effectiveness of LAMill is verified by comparing the conventional machining. Down cut milling is recommended for the case of Inconel 718.